Estudio de prefactibilidad para la instalación de una planta productora de muebles multifunción de dormitorio, elaborados a base de melamina - Arenas Martos, Natali (2019)
The present study seeks to apply the tools and concepts used in the industrial engineering career for the implementation of a bedroom furniture production plant. This product has as a target market in Metropolitan Lima, addressing the socioeconomic levels B and C1,. Also, it is segmented according to age range to people from 18 to 55 years. The product is sold unarmed at a price of S / .1 203.60, which includes installation and shipping. The plant is located in the Villa el Salvador district in the province of Metropolitan Lima. A maximum production capacity of 5,243 units was determined, the bottleneck being the stage of the drilling process, in addition to having a semi-automatic production process. Regarding the financial and economic analysis, an investment of 1 008 629 soles was determined, in which 60% corresponds to external financing by a banking entity. A financial NPV of 944,102 soles, a financial IRR of 74% and a cost benefit value equal to 3.34 soles were estimated in the project's life horizon corresponding to 6 years, in addition to an estimated investment recovery period of 2 years, 7 months and 2 days, demonstrating the financial viability of the project. Finally, a positive effect on the contribution to society is determined since an aggregate value of 6,529,182.40 soles and a capital density of 18,678.31 soles / employment is generated.